2018
DOI: 10.1017/s0033291718000065
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence: a systematic review and meta-analysis of psychological treatments for individuals on sick leave due to common mental disorders

Abstract: Sick leave due to common mental disorders (CMDs) increase rapidly and present a major societal challenge. The overall effect of psychological interventions to reduce sick leave and symptoms has not been sufficiently investigated and there is a need for a systematic review and meta-analysis of the field. The aim of the present meta-analysis was to calculate the effect size of psychological interventions for CMDs on sick leave and psychiatric symptoms based on all published randomized controlled trials. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 49 publications
4
59
1
1
Order By: Relevance
“…The findings show that there is a small but significant effect of psychological interventions on SA and RTW overall. This result is in line with other, similar reviews (Arends et al, 2012;Doki et al, 2014;Nigatu et al, 2016;Salomonsson et al, 2018). Thus, our findings support that psychological interventions might have an effect for patients on SA due to common mental disorders and musculoskeletal pain, however the small effect is not satisfactory.…”
Section: Interpretation Of Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings show that there is a small but significant effect of psychological interventions on SA and RTW overall. This result is in line with other, similar reviews (Arends et al, 2012;Doki et al, 2014;Nigatu et al, 2016;Salomonsson et al, 2018). Thus, our findings support that psychological interventions might have an effect for patients on SA due to common mental disorders and musculoskeletal pain, however the small effect is not satisfactory.…”
Section: Interpretation Of Resultssupporting
confidence: 90%
“…Previous meta-analyses have not been unanimous but have pointed in different directions, possibly due to lack of power because of low numbers of included studies. Despite higher power in this meta-analysis, the effect sizes found are not larger than those found in previously (Arends et al, 2012;Cochrane et al, 2017;Doki, Sasahara, & Matsuzaki, 2014;Meijer, Sluiter, & Frings-Dresen, 2005;Nieuwenhuijsen et al, 2014;Nigatu et al, 2016;Salomonsson, Hedman-Lagerlof, & Ost, 2018). It should be noted that most trials did not specifically target RTW which can be one explanation for the small ESs.…”
Section: Discussioncontrasting
confidence: 69%
“…The effect size was small, but psychological interventions were found to be more effective than treatment as usual (TAU) for reducing sick leave and symptoms. There was no significant difference between work-focused interventions, PST or CBT (36).…”
Section: Psychological And/or Stress-reducing Interventions + Workplamentioning
confidence: 73%
“…Previous research has shown that there seems to be an overall positive effect of psychological interventions in reducing sick leave (Nigatu et al ., ; Salomonsson, et al ., ), but the effects are small and there may be disorder specific differences (Arends et al ., ; Nieuwenhuijsen et al ., ). In the present study, there was no difference in reduced sick leave between treatments for the Stress subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Sick leave or absenteeism is one of the most costly consequences of CMDs (OECD, ). Meta‐analyses show that psychological interventions have a small but significant effect in reducing sick leave compared to care as usual (CAU) for individuals with CMDs (Nigatu, Liu, Uppal et al ., ; Salomonsson, Hedman‐Lagerlöf, & Öst, ). For depressed individuals, both CBT and an added work‐directed intervention have been found to reduce sick leave more than CAU (Nieuwenhuijsen, Faber, Verbeek et al ., ).…”
Section: Introductionmentioning
confidence: 99%